Optimizing surgical margins in the treatment of eyelid Merkel cell carcinoma: a tertiary center experience and literature review - Strianese, Diego; Barbato, Claudio; Troisi, Mario; Lanni, Vittoria; Damiano, Vincenzo; Di Crescenzo, Rosa Maria; Passaro, Maria Laura; D’Aponte, Antonella; Nubi, Raffaele; Conson, Manuel; Cohen, Dana; Mariniello, Giuseppe; et al. (Frontiers in Ophthalmology, 2025)
BackgroundMerkel cell carcinoma (MCC) of the eyelid is rare and aggressive. Diagnostic delay and inadequate excision may promote early nodal spread. We assessed the influence of surgical margins and re-excision timing on outcomes, supported by a PRISMA-guided systematic review on metastatic risk.MethodsA single-center retrospective series (2012–2024) included 9 histologically confirmed eyelid MCCs, analyzing presentation, treatment, and outcomes. Surgical strategies were classified as one-step wide local excision (1WLE, ≥5 mm), two-step wide local excision (2WLE) with early (E2WLE, ≤2 months) or late (L2WLE, 6 months) re-excision, and insufficient margin excision (IME, <2 mm without re-excision). A systematic review identified periocular MCC cases with individual-level data on margins and outcomes.ResultsPatients (median age 71.8 years, range 42–92; 89% female) all presented with solitary nodules on the upper eyelid, and were node-negative and metastasis-free at diagnosis, consistent with AJCC 8th clinical stage I–IIA.Median follow-up was 48 months (IQR 12–120). Treatments included 1WLE (n=4), 2WLE (n=3; 2 E2WLE, 1 L2WLE), and IME (n=2). Three patients (33%) developed cervical lymph node metastases within 1–3 months: one after L2WLE (fatal at 12 months) and two after IME. Both IME patients showed marked responses to Avelumab. Of the remaining six, four (67%) remained disease-free and two (33%) died of unrelated causes. Metastatic risk was significantly higher after IME versus sufficient margins (p=0.0119). In the PRISMA-guided review (76 eyelid MCC), insufficient margins correlated with adverse outcomes; in a subset without baseline metastasis (n=39), insufficient margins increased risk of recurrence/metastasis (OR 10.56; 95% CI 1.84–77.24; Fisher’s exact p=0.002).ConclusionIn eyelid MCC, adequate margins at first surgery or early re-excision are crucial to prevent early nodal spread. Our findings emphasize the prognostic value of surgical adequacy and support incorporating wide excision into initial management. Further multicenter studies are warranted to define evidence-based management pathways, improve long-term outcomes, and clarify the role of checkpoint inhibition in periocular MCC.